PELATIHAN PENGOLAHAN SAMPAH UNTUK MEMPRODUKSI KOMPOS DAN MAGGOT BSF DI PERUMAHAN BUMI TUNGGULWULUNG INDAH KOTA MALANG - Sumiadji Sumiadji; Basuki Rachmat; Endah Suwarni; Fita Setiati; Futuh Handoyo; Edi Winarto; Padma Adriana Sari (Universitas Trisakti, 2022)
The community service activities are carried out in the Bumi Tunggulwulung Indah (BTWI) housing where all the residents in this housing namely RT 015-RW 001, Tunggulwulung, Lowokwaru, Malang City. There are problems faced by BTWI residents, the main points can be identified as follows: (1) there is a fairly large volume of waste in the BTWI environment, both leaf waste and kitchen waste (2) dry waste disposal (dry twigs and leaves) requires regular costs. The transportation of kitchen waste is sometimes constrained so that it accumulates and causes pollution, and (3) the accumulation and full volume of waste in the Temporary Shelter (TPS) in the Tunggulwulung sub-district. The results of the residents' deliberation agreed to form a partner team to work with the implementing team for community service activities. The purpose of this waste management training is expected to (1) improve the understanding and behavior of residents in processing waste, (2) reduce the amount of waste that must be transported, and (3) increase the economic value of waste into compost and BSF maggot. The methods applied in community service activities are counseling, training and monitoring. The results of the activity showed that the implementation of the extension succeeded in providing understanding and knowledge about waste management to activity partners. The results of the training were able to overcome the waste problem, reduce the cost of transporting waste and change the economic value of waste into compost and maggot as an alternative feed for catfish supplements.